Development of Low‐Shrinkage Polymers by Using Expanding Monomers. Issue 1 (August 2017) - Acosta Ortiz, Ricardo; Savage Gomez, Amy Grace; García Valdez, Aída E.; Aguirre Flores, Rafael; Sangermano, Marco
Abstract : This review reports advances in research related to the development of novel spiroorthocarbonates and the study of their performance in reducing or eliminating the shrinkage observed in the polymerization of epoxy and acrylic monomers.